2018
DOI: 10.4049/jimmunol.1701489
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s Tyrosine Kinase Is Not Essential for B Cell Survival beyond Early Developmental Stages

Abstract: Bruton's tyrosine kinase (Btk) is a crucial regulator of B cell signaling and is a therapeutic target for lymphoma and autoimmune disease. BTK-deficient patients suffer from humoral immunodeficiency, as their B cells fail to progress beyond the bone marrow. However, the role of Btk in fully developed, mature peripheral B cells is not well understood. Analysis using BTK inhibitors is complicated by suboptimal inhibition, off-target effects, or failure to eliminate BTK's adaptor function. Therefore a mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…The differences in TD immune responses between IPMK cKO and Btk-deficient mice might be, at least in part, due to their difference in B cell development. These differences in TD immune responses between the two mice is in line with the results that inducible Btk deletion in mature B cells, in which B cell development is normal, results in a milder phenotype in immune responses than that by Btk deletion in the whole body (46).…”
Section: Discussionsupporting
confidence: 84%
“…The differences in TD immune responses between IPMK cKO and Btk-deficient mice might be, at least in part, due to their difference in B cell development. These differences in TD immune responses between the two mice is in line with the results that inducible Btk deletion in mature B cells, in which B cell development is normal, results in a milder phenotype in immune responses than that by Btk deletion in the whole body (46).…”
Section: Discussionsupporting
confidence: 84%
“…In diseased NZB/W mice, marginal zone B cells were increased, as well, but their numbers were not affected significantly by evobrutinib treatment. The lack of effect of evobrutinib on marginal zone B cells is in line with the observation that an inducible deletion of BTK in adult animals does not affect these cells (69). In contrast, published data for the covalent reversible BTK inhibitor PF-06260112 showed an 11-fold and 20-fold reduction of marginal zone and B1 B cells, respectively, in a nonaccelerated NZB/W lupus model.…”
Section: Discussionsupporting
confidence: 78%
“…However, in these mice, BTK is absent throughout development. Experiments in which BTK was knocked down after B cell subsets were established showed that follicular B cell numbers dropped within 5 wk of BTK depletion to the low levels observed in global BTK knockouts (69). The fact that evobrutinib normalized follicular B cell numbers without signs of depletion may be explained by the remaining scaffolding function of BTK, even when its kinase activity is blocked by evobrutinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations